Capital structure inconclusiveness: evidence from Malaysia, Thailand and Singapore - Haron, Razali (Emerald Group Publishing, 2014)
The purpose of this paper of this study is to examine the possible factors contributing to the issue of inconclusiveness in capital structure studies. This study also attempts to provide logical explanations to the unresolved issue of inconsistencies in the relationship between factors identified and leverage in capital structure studies. Comparisons are also made between the emerging market and the developed market to see whether the findings are consistent with both market landscapes. This study employs two models in its methodology which are static and dynamic models to examine the effects of using different models in the study. The fixed effect model and partial adjustment model represent the static and dynamic models, respectively. The dynamic model is estimated using generalized method of moments. This study also uses six definitions of leverage to examine the impact of using different leverage definition in capital structure studies. To test the robustness of the findings comparison were made with past studies done by other researchers on developed markets. This study found that the use of different models (with the same leverage definition) and different leverage definitions (using the same model) give different results including signs. Inconsistencies were more obvious in the different leverage definitions (using the same model)compared to the use of different models (with the same leverage definition). There was also evidence that the findings were consistent with both the emerging and the developed markets as other studies on developed markets also report inconsistent results when using different models and different leverage definitions. The sample chosen focussed only on firms in three emerging markets (Malaysia, Thailand and Singapore) thus it may not be sufficient for generalization. The issue of inconclusive results and findings in capital structure studies keeps recurring but no study has been done to further understand the issue. Using data from the selected countries, this paper attempts to fill this gap in the literature.